PENELITIAN KOMUNIKASI PENDEKATAN KUANTITATIF DAN KUALITATIF BERBASIS INTERNET - Mudjiyanto, Bambang (Istek Widuri Jakarta, 2017)
Departing from the phenomenon is still relatively the lack of research-focused research on the phenomenon of communication in the internet media, this paper focuses its discussion directed at the problem of communication research implementation of quantitative and qualitative approach based on internet. From the results of the discussion concluded that basically the phenomenon of communication that occurs through the medium of the Internet can be reviewed through research with quantitative approach and qualitative approach. In research with quantitative approach, which distinguish it is on the type of research, namely between the type of correlative research and descriptive type research. This is because it relates to the nature of the sampling. While in research with a qualitative approach, in relation to the object 'text', in addition to its genre is relatively very much, the level of analysis is also so relatively easy to develop.